Spatio-Temporal Patterns of Crime against Women in Darjeeling District: Examining Spatio-Temporal Patterns of Crime against Women in Darjeeling District: Insights from Regional and Block Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
An endeavor has been made to examine crime against women that happened during 2004 to 2014 in Darjeeling district. Information relating to contemplate was gathered from the workplace of Superintendent of Police, Darjeeling and Commissioner ate of Police, Siliguri. Examination is done at both territorial and square level. At provincial level greatest crime against women happened in terai than the slopes and at block it was found in Matigara, Naxalbari and Phanisdewa. In terai level of crime against women is more than the slopes. Populace, thickness of populace, rbanization, temperature, and so on is high in terai and it has a genuine bearing on the pace of crime against women.